Odpowiedzi

2010-04-10T18:52:46+02:00
6x +8y- 12=0
-3x- 4y+6=0 / x2

6x + 8y-12= 0
-6x -8y+12=0

x= 0
y=o
2010-04-10T19:00:48+02:00
6x+8y-12=0
-3x-4y+6=0 /:-3

6x+8y-12=0
x+4/3y-2=0

6x+8y-12=0
x=-4/3y+2

6(-4/3y+2)+8y-12=0
-8y+12+8y-12=0
0=0 nieskonczenie wiele rozwiazan

x=-4/3y+2
x=2
y=0


4y=-8+6
-3x+2y=-2 /:2

4y=-8+6
-3/2x+y=-1


4y=-8+6
y=-1+3/2x

4(-1+3/2x)=-8+6
-4+6x=-8+6
6x=2 /:6
x=1/3

y=-1+3/2x
y=-1+3/2*1/3
y=-1/2
x=1/3

chyba dobrze=]=] jak czegoś nie kapujesz pisz na priva=]=]
buziak:*
2010-04-10T19:50:27+02:00
A)
6x+8y-12=0
-3x-4y+6=0

6x+8y=12|:6
-3x-4y=-6

x=2-1⅓y
-3(2-1⅓y)-4y=-6
-6+4y-4y=-6
0=0


b)
4y=-8+6x
-3x+2y=-2 |:2

-6x+4y=-8
y=-1+1,5x

-6x+4(-1+1,5x)=-8
-6x-4+6x=-8
0≠-4